Globalization and food security in Sub-Saharan Africa - Shang, Yuxiao; Lv, Yeming; Chen, Zhenghui; Bassey, Rowland; Aderemi, Timothy A.; Enilolobo, Oluwafemi (Frontiers in Sustainable Food Systems, 2024)
The research aimed to assess the impact of globalization and innovation on food security in Sub-Saharan Africa (SSA) between 2001 and 2021. The study utilized secondary data from the World Development Indicators to analyze the relationship. Food security was measured in terms of accessibility and availability, represented by the "Food Production Index (2014-2016=100)" and "Gross Domestic Product per Capita, PPP, Dissemination (constant 2017 international $)" respectively. The research employed a two-step System Generalized Method of Moments (GMM) to evaluate the data. The results indicated that globalization showed a direct and statistically insignificant influence on food security availability, but it had a negative and significant effect on food security accessibility. On the other hand, innovation had a direct but statistically insignificant effect on food security availability, while it had a positive and significant impact on food security accessibility. The interaction between globalization and innovation had an indirect but significant effect on food security availability and a direct and significant effect on food security accessibility. Additionally, the study found that arable land and population growth significantly influenced the availability aspect of food security, while arable land indirectly affected the accessibility aspect. Population had a direct but statistically insignificant effect on the accessibility measure of food security. Based on these findings, the study recommends that the governments of SSA countries and other stakeholders should adopt and operate integrated policy approaches that captures the diverse effects that globalization has on food security.